Tortuosity of parent artery predicts in-stent stenosis after pipeline flow-diverter stenting for internal carotid artery aneurysms - Gao, Haibin; You, Wei; Wei, Dachao; Lv, Jian; Sun, Wei; Li, Youxiang (Frontiers in Neurology, 2022)
Background and purpose The relationship between the tortuosity of the parent artery and treatment outcomes is not well established. We investigate the association between parent artery tortuosity and flow diverter (FD) treatment outcomes in patients with internal carotid artery aneurysms in this study. Methods A retrospective review study was conducted to identify all patients with internal carotid artery aneurysms who were implanted with Pipeline embolization device (PED) between 2016 and 2020. The relationship between parent artery tortuosity and aneurysm complete occlusion (CO) and in-stent stenosis (ISS) was analyzed. The mathematical parameters “Curvature”, “torsion”, and “DM” extracted from the parent artery were utilized to quantify the parent artery tortuosity. A vascular narrowing of greater than 25% was categorized as ISS. Logistic regression analysis was used to identify significant independent predictors. Furthermore, we compared the performance of four machine learning algorithms and Logistic Regression model in predicting ISS. Results This research included 62 patients who with internal carotid artery aneurysms. In 49 (79%) cases, follow-up angiography (mean follow-up duration 11.7 ±7.3 months) revealed CO of the aneurysm. ISS was detected in 22 (35.5%) cases. According to univariate analysis, parent artery tortuosity and other variables were not associated with CO (p > 0.1). Maximum curvature (OR = 1.084; 95% CI, 1.008–1.165; p = 0.03) and DM (OR = 0.01; 95% CI, 0–0.488; p = 0.02) exhibited strong independent associations with ISS in multivariate analysis. The SVM model is superior to the conventional Logistic Regression model and the other models in predicting ISS. Conclusions The tortuosity of the parent artery may affect the treatment outcome of FD stenting. We found that parent artery tortuosity was associated with ISS, but not with aneurysm complete occlusion following PED stenting for internal carotid artery aneurysms in this study. Parent arteries with higher maximum curvature and lower DM were more likely to develop ISS.